Theater Contribution To World Politics Of The SixteenthCentury England Reflected At William Shakespeare's TheLife And The Death Of King John Drama(1595): A Sociological Approach - Pradini, Mei Dian, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M. Hum (2014)
This study is about theatre contribution to world politics of the sixteenth century England. The problem of this study is how theatre contribution to world politics of sixteenth century England is reflected at William Shakespeare's The Life and Death of King John Drama viewed from sociological approach. The objectives of this study are identify the structural elements and the sociological perspective in The Life and Death of King John drama. The object of the study is William Shakespeare's The Life and Death of King John drama (1595). It is analyzed by using a sociological perspective. This study is qualitative research. There are two sources that are needed to do this research, namely: primary data sources and secondary data sources. The primary data sources are William Shakespeare's The Life and Death of King John drama (1595). The secondary data sources from other sources related the study, such as: website, dictionary, some book that support the analysis. The result of the study shows the following conclusions. First,The Life and Death of King Johnhas big contribution to make England people to keepEngland from any threat and bring winning for England. Second, the theatre contribution for England, people wereusing communication to solve problems.